The scientometric evaluation of the institutional research: The Akdeniz universities- part 1 - Konur, Özcan (SILA SCIENCE, 2013)
The scientometric analysis of the research has become one of the most used methods to assess the research performance of the scholars, departments, faculties, universities, countries, and journals in recent years. However, there has not been an extensive scientometric evaluation of the institutional research carried out by the universities in the Akdeniz (Mediterranean) region of Turkey with wide ranging socioeconomic development indices, to examine the development of the regional research over time. Hence, the purpose of this study was to carry out a scientometric evaluation of the research performed by these regional universities using three indices in a series of three papers. In the first part of these serial papers, it was found that there were 13 universities founded in 8 cities between 1973 and 2011. There were 3,829 senior members of the academic staff in these universities, comprising 8.5% of the national academic force. One, one, five, three, and three of these universities were pre-1980, 1980, 1990, 2000, and 2010 universities, respectively. 19%, 22%, 54%, and 5% of the regional academic force was employed by the pre-1980, 1980, 1990, and 2000 universities, respectively. The 2010 universities had no academic staff as of November 2010. Cukurova University was the first established university of the region in Adana in 1973. The top university was Akdeniz University (22%) followed by Suleyman Demirel University (21%), Cukurova University (19%), Mersin University (14%), and Mustafa Kemal University (11%). These universities were founded in the Akdeniz region of Turkey with varying socio-economic development indices (SEDI) ranging from 4 for Antalya to 60 for Kahramanmaras. Antalya and Mersin had 3 regional universities each whilst Adana had 2 universities and the other cities had only one university each. The state universities adapted an aggressive expansionist policy whilst the foundation universities did not. In this respect, Suleyman Demirel University's rapid expansion was especially notable becoming the second largest university of the region although it was founded in 1992. Akdeniz University was notable with its aggressive expansionist policies in the towns like Alanya. The first four groups of faculties including faculties of medicine employed 60.1% of the academic staff. The results found in the first part suggest that there was a close structure-research performance relationships for these universities hinting the strong effect of the formal and informal rules adapted by these universities on their respective research productivity following North's new institutional theoretical framework.
Keywords: Scientometrics; A&HCI; Web of Knowledge; Turkey; SSCI; SCIE; Incentive structures; Research evaluation geography; Research productivity; Akdeniz Universities